Black-White variation in the relationship between early educational experiences and trajectories of cognitive function among US-born older adults - Katrina M. Walsemann; Eleanor M. Kerr; Jennifer A. Ailshire; Pamela Herd (Elsevier, 2022)
Black adults face a substantially higher risk for dementia in later life compared to their White peers. Given the critical role of educational attainment and cognitive function in later life dementia risk, this paper aims to determine if early educational experiences and educational attainment are differentially related to trajectories of cognitive status across race and if this further varies by education cohort. We use data from the Life History Mail Survey (LHMS) and prospective data on cognition from the Health and Retirement Study (HRS). We restrict our sample to Black and White US-born adults who provided at least one measure of cognitive status from 1995/6-2016. We find evidence of Black-White differences in the association between educational experiences and level of cognitive function, episodic memory, and working memory, but little evidence of Black-White differences in these associations with decline. Having a learning problem was associated with lower levels of cognitive function, episodic memory, and working memory for White and Black older adults, but was more strongly related to these outcomes among Black older adults. Further, the Black-White difference in this association was generally found in older cohorts that completed schooling after enactment of federal policies that improved educational resources for children with learning disabilities. Attending racially discordant schools was positively associated with level of these cognitive outcomes for Black older adults but not for White older adults. We also find that the educational gradient in level of cognitive function was larger for Black compared to White older adults in older cohorts not benefiting from the Brown v Board of Education decision but was similar for Black and White older adults attending school in the post-Brown era.